New names in Phyllopodium (Scrophulariaceae-Manuleae) - Hilliard, O. M. (Edinburgh Journal of Botany, 2010)
Phyllopodium Benth. subgen. Leiospermum Hilliard is newly described; Selago cephalophora Thunb., S. phyllopodioides Schltr., and Polycarena hispidula Thell. are transferred to Phyllopodium.